Heat and Wear Generation for Rolling Contacts - Sextro, Walter (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Development and Experimental Validation of a Point Contact Model for Dynamical Problems with Friction - Sextro, Walter (ASME Design Engineering Technical Conferences)

Localization in Nonlinear Mistuned Systems with Cyclic Symmetry - Sextro, Walter; Popp, Karl; Krzyzynski, Tomasz (Nonlinear Dynamics)
In forced systems with cyclic symmetry localization can occur due toparameter uncertainties. Often, Monte-Carlo simulations are used to findregions, where the system response is sensitive to parameteruncertainties. These simulations require a large computation time.Therefore, an approximate method to calculate the envelopes of thefrequency response functions is developed in this paper. An example of anonlinear system with cyclic symmetry is a bladed disk assembly withfriction dampers. Friction dampers can be installed underneath the bladeplatforms of turbine blades. Due to dry friction and the relative motionbetween blades and dampers, energy is dissipated, which results in areduction of blade vibration amplitudes. By optimizing the mass of thefriction dampers, the best damping effects are obtained, which lead toan increase in the reliability of the turbine. In this paper, thecalculated response of a mistuned bladed disk assembly with frictiondampers is discussed. An approximate method is developed to calculatethe envelopes of the corresponding frequency response function forstatistically varying eigenfrequencies of the blades. Regions wherelocalization can occur with a high probability, are calculated by thismethod.
Keywords: bladed disk assembly; mistuning; sensitivity; localization

Piezoelektrische lineare Schwingungsantriebe - Wallaschek, Jörg; Hemsel, Tobias (Special Antriebstechnik)

Analysing capacity improvements in wireless networks by relaying - Karl, Holger; Mengesha, Seble (Proc. of IEEE Intl. Conf. on Wireless LANs and Home Networks)

Relative jitter packet scheduling for differentiated services - Quynh, T; Karl, Holger; Wolisz, Adam; Rebensburg, Klaus (Proc. 9th IFIP Conf. Perf. Modeling and Eval. of ATM & IP Networks)

The promise of workplace training for non-college-bound youth: Theory and evidence from German apprenticeship - Clark, Damon; Fahr, Rene (CEP Discussion Paper No. 528)

Komponentenorientierte Softwareentwicklung in Softwareunternehmen: Konzeption eines Vorgehensmodells zur Einführung und Etablierung - Schryen, Guido

British Political Speeches from Churchill to Blair

The randomized z-buffer algorithm - Wand, Michael; Fischer, Matthias; Peter, Ingmar; Meyer auf der Heide, Friedhelm; Straßer, Wolfgang (Proceedings of the 28th annual conference on Computer graphics and interactive techniques - SIGGRAPH '01)
We present a new output-sensitive rendering algorithm, the randomized z-buffer algorithm. It renders an image of an arbitrary three-dimensional scene consisting of triangular primitives by reconstruction from a dynamically chosen set of random surface sample points. This approach is independent of mesh connectivity and topology. The resulting rendering time grows only logarithmically with the numbers of triangles in the scene. We were able to render walkthroughs of scenes of up to 10^14 triangles at interactive frame rates. Automatic identification of low detail scene components ensures that the rendering speed of the randomized z-buffer cannot drop below that of conventional z-buffer rendering. Experimental and analytical evidence is given that the image quality is comparable to that of common approaches like z-buffer rendering. The precomputed data structures employed by the randomized z-buffer allow for interactive dynamic updates of the scene. Their memory requirements grow only linearly with the number of triangles and allow for a scene graph based instantiation scheme to further reduce memory consumption.

Data Management in Networks - Meyer auf der Heide, Friedhelm (Graph-Theoretic Concepts in Computer Science)

Parallel Bridging Models and Their Impact on Algorithm Design - Meyer auf der Heide, Friedhelm; Wanka, Rolf (Computational Science - ICCS 2001)

The Algorithms Behind GAIO — Set Oriented Numerical Methods for Dynamical Systems - Dellnitz, Michael; Froyland, Gary; Junge, Oliver (Ergodic Theory, Analysis, and Efficient Simulation of Dynamical Systems)

Extracting Dynamical Behavior via Markov Models - Froyland, Gary (Nonlinear Dynamics and Statistics)

Rigorous computation of topological entropy with respect to a finite partition - Froyland, Gary; Junge, Oliver; Ochs, Gunter (Physica D: Nonlinear Phenomena)

An adaptive subdivision technique for the approximation of attractors and invariant measures: proof of convergence - Junge, Oliver (Dynamical Systems)

Algorithms — ESA 2001, 9th Annual European Symposium Århus, Denmark

Glimpses into the Future of Computer Science Education - Domik, Gitta (J. (UCS))

The numerical detection of connecting orbits - Dellnitz, Michael; Junge, Oliver; Thiere, Bianca (Discrete & Continuous Dynamical Systems - B)

Object-oriented domain specific compilers for programming FPGAs - Mencer, Oskar; Platzner, Marco; Morf, Martin; J. Flynn, Michael (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

Implementation of a Rake Receiver Architecture into a Galileo Receiver - Bischoff, R.; Haeb-Umbach, Reinhold; Schulz, W.; Heinrichs, G. (1st ESA Workshop on Satellite Navigation User Equipment Technology (Navitec 2001))

Automatic generation of phonetic regression class trees for MLLR adaptation - Haeb-Umbach, Reinhold (IEEE Transactions on Speech and Audio Processing)
In this paper, it is shown that a correlation criterion is the appropriate criterion for bottom-up clustering to obtain broad phonetic class regression trees for maximum likelihood linear regression (MLLR)-based speaker adaptation. The correlation structure among speech units is estimated on the speaker-independent training data. In adaptation experiments the tree outperformed a regression tree obtained from clustering according to closeness in acoustic space and achieved results comparable with those of a manually designed broad phonetic class tree
Keywords: acoustic space; adaptation experiments; automatic generation; bottom-up clustering; broad phonetic class regression trees; correlation criterion; correlation methods; maximum likelihood estimation; maximum likelihood linear regression based speaker adaptation; MLLR adaptation; pattern clustering; phonetic regression class trees; speaker-independent training data; speech recognition; speech units; statistical analysis; trees (mathematics)

Multiclass linear dimension reduction by weighted pairwise Fisher criteria - Loog, M.; Duin, R.P.W.; Haeb-Umbach, Reinhold (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We derive a class of computationally inexpensive linear dimension reduction criteria by introducing a weighted variant of the well-known K-class Fisher criterion associated with linear discriminant analysis (LDA). It can be seen that LDA weights contributions of individual class pairs according to the Euclidean distance of the respective class means. We generalize upon LDA by introducing a different weighting function
Keywords: approximate pairwise accuracy; Bayes error; Bayes methods; error statistics; Euclidean distance; Fisher criterion; linear dimension reduction; linear discriminant analysis; pattern classification; statistical analysis; statistical pattern classification; weighting function

Experience-based decision making and learning from examples - Hüllermeier, Eyke (In Proceedings SOR-01 Symposium on Operations Research, Duisburg, Germany)

Ultraschallgeschwindigkeitsmessung zum Bioprozessmonitoring - Cha, Y. L.; Hitzmann, Bernd; Bellgardt, Karl-Heinz; Daur, Peter-Christoph; Henning, Bernd
In diesem Beitrag werden Messungen und Auswertungen der Ultraschallgeschwindigkeitsmessung zur Überwachung von Hefekultivierungen vorgestellt. Die Ultraschallgeschwindigkeit ist abhängig von Biomasse-, Glukose- und Ethanolkonzentration, aber auch von anderen Bioprozessvariablen. Um den Einfluss von Blasen auf das Signal zu reduzieren, wurde der Ultraschallsensor in einem Bypass-System eingesetzt. Es wurden Messungen sowohl im Flow- als auch Stop-Flow-Betrieb durchgeführt. Um die richtigen Informationen aus diesem unspezifischen Signal zu erhalten, wurde ein multilineares Regressionsmodell berechnet, wobei die Biomasse-, Glukose- und Ethanolkonzentration als unabhängige Variablen dienten. Ein Beispiel der Ergebnisse ist in Abbildung eins gezeigt. Es sind die Biomasse-, Glukose- und Ethanolkonzentration während einer Saccharomyces cerevisiae Kultivierung dargestellt. Die Parameter des multilinearen Regressionsmodells wurden durch Verwendung der Daten aus der dargestellten Kultivierung identifiziert. Wird dieses Modell zur Auswertung auf die Signale anderer Prozesse übertragen, ist das Ergebnis ähnlich, jedoch vergrößert sich der Fehler der Schätzung. Die Ergebnisse sowie Erfahrungen werden ausführlich in dem Beitrag diskutiert.

Quality inspection and characterisation of ultrasonic sensor properties using a PC-controlled scanning measuring system - Henning, Bernd; Prange, Stefan; Dierks, Karsten; Daur, Peter-Christoph
Nowadays the use of ultrasonic sensors for process control for flow, level or concentration measurement is wide spread. In this application there are high demands for a defined and stable quality of the properties of such ultrasonic sensors. For the detailed investigation and characterization of ultrasonic sensor properties an efficient PC-controlled measuring system has been developed at ifak. In this report this new high performance approach will be presented to make the vibrating ultrasonic sensor surface and also the sound field in front of acoustic sensors in liquids visible.

Vom Modellieren zum Gestalten - Objektorientierung als Impuls für einen neuen Informatikunterricht? - Schulte, Carsten (Informatica Didactica)

Aufgabenbereiche der Medienbildung im Informatikunterricht - Schulte, Carsten; Scheel, Olaf (INFOS)

Possibilistic instance-based learning - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)

Implication-based fuzzy association rules - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)

Instance-based prediction in the framework of possibility theory - Hüllermeier, Eyke; Dubois, D.; Prade, H. (In Proceedings of Workshop on Soft Computing in Case-Based Reasoning, Vancouver, Canada)

Ertragsteuerliche Vorteilhaftigkeitsüberlegungen bei der Verschmelzung einer Kapitalgesellschaft auf eine Personengesellschaft - König, Rolf; Magerkurth, Tanja; Sureth-Sloane, Caren (Steuern und Bilanzen)

BilanzReForm, Steuerbelastungsrechnungen am PC - König, Rolf; Sureth-Sloane, Caren

Implication-based fuzzy association rules - Hüllermeier, Eyke (in Proceedings PKDD-01 5th European Conference on Principles and Practise of Knowledge Discovery in Databases, Freiburg, Germany)

Fuzzy association rules: Semantic issues and quality measures - Hüllermeier, Eyke (in Proceedings of the International Conference on Computational Intelligence 7th Fuzzy Days, Dortmund, Germany)

Toward the representation of implication-based fuzzy rules in terms of crisp rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (in Proceedings IFSA/NAFIPS-2001 Joint 9th World Congress of the International Fuzzy Systems Association and 20th Internatinonal Conference of the North American Fuzzy Information Processing Society, Vancouver, Canada)

Europäisches Arbeitsrecht - Krimphove, Dieter

Similarity-based inference as evidential reasoning - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Machinelles Lernen und Komplexität - Hüllermeier, Eyke (Ökonomie und Gesellschaft, Jahrbuch 17: Komplexität und Lernen)

Empirische Überprüfung eines synergetischen Konjunkturmodells - Kraft, M.; Hüllermeier, Eyke; Weise, P. (Studien zur Evoltorischen Ökonomik IV)

Strategisches Personalmanagement in globalen Unternehmen

Vom Gründungsmanagement bis zum Neuen Markt

Two-Dimensional Test Data Compression for Scan-Based Deterministic BIST - Liang, Hua-Guo; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

IT-Unterstützung im Customer Relationship Management - Trier, Matthias (Industrie Management Journal)

Dynamically Reconfigurable Processors - Enzler, Rolf; Platzner, Marco

The influence of proportional jitter and delay on end to end delay in differentiated service network - Quynh, Thu Ngo; Karl, Holger; Wolisz, Adam; Rebensburg, Klaus (Network Computing and Applications, 2001. NCA 2001. IEEE International Symposium on)

Circular flow numbers of regular multigraphs - Steffen, Eckhard (J. Graph Theory)

On bicritical snarks - Steffen, Eckhard (Math. Slovaca)

Atomic structure and optical anisotropy of III–V(001) surfaces - Esser, N.; Schmidt, Wolf Gero; Cobet, C.; Fleischer, K.; Shkrebtii, A. I.; Fimland, B. O.; Richter, W. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Structure and Energetics of P-rich GaP(001) Surfaces - Pulci, O.; Schmidt, Wolf Gero; Bechstedt, F. (physica status solidi (a))

On the origin of resonance features in reflectance difference data of silicon - Hingerl, K; Balderas-Navarro, R.E; Bonanni, A; Tichopadek, P; Schmidt, Wolf Gero (Applied Surface Science)

Terrace and step contributions to the optical anisotropy of Si(001) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Physical Review B)

Ladwig, Bernd, Militärische Interventionen zwischen Moralismus und Legalismus (Deutsche Zeitschrift für Philosophie, Berlin, 48, 2000) - Ficara, Elena (Servizio web italiano per la filosofia)

Schmücker, Reinold, Gibt es einen gerechten Krieg? (Deutsche Zeitschrift für Philosophie, Berlin, 48 2000) - Ficara, Elena (Servizio web italiano per la filosofia)

Wohlrapp, Harald, Krieg für Menschenrechte? (Deutsche Zeitschrift für Philosophie, Berlin, 48) - Ficara, Elena (Servizio web italiano per la filosofia)

Carter, Ian, L’idea di eguaglianza, Milano 2000 - Ficara, Elena (Bollettino telematico della filosofia politica)

Problemi della soggettività nella storia e nel presente - Ficara, Elena (Giornale Critico della Filosofia Italiana)

Leibniz’ Pragmatismus - Peckhaus, Volker (VII. Internationaler Leibniz-Kongreß. Nihil sine ratione. Mensch, Natur und Technik im Wirken von G.W. Leibniz. Schirmherrschaft: Der Regierende Bürgermeister von Berlin)

,Mein Glaubensbekenntnis‘. Leonard Nelsons Brief an David Hilbert - Peckhaus, Volker (Mathematik im Wandel. Anregungen zu einem fächerübergreifenden Mathematikunterricht, Bd. 2)

Die regressive Methode - Peckhaus, Volker (Zwischen traditioneller und moderner Logik. Nichtklassische Ansätze)

Dialog mit Hindernissen: Philosophie und Mathematik - Peckhaus, Volker (Von der Antike bis zur Gegenwart. Erlanger Streifzüge durch die Geschichte der Philosophie)

Active Common-Mode Voltage Cancellation for Three-Phase PWM Rectifier/Inverter Systems based on a New Topology - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert (Proc. 16th IEEE Applied Power Electronics Conf. (APEC))

High Dynamic Control of a Three-Level Voltage Source Converter Drive with Synchronous Motor and Active Front End - Böcker, Joachim; Janning, Jörg; Jebenstreit, Helmut (EPE’01, Graz)

Generalization of orthogonality principle to model solenoidal wound multiwinding transformers - Wallmeier, P. (Conference Record of the 2001 IEEE Industry Applications Conference. 36th IAS Annual Meeting (Cat. No.01CH37248))

Linear Drive System for the NBP Railway Carriage - Henke, M,; Yang, B.; Grotstollen, H.

CAE-tool for optimizing development of switched mode power supplies - Fröhleke, N.; Hahm, D.; Mundinger, H.; Njiende, H.; Wallmeier, P.; Puder, H. (APEC 2001. Sixteenth Annual IEEE Applied Power Electronics Conference and Exposition (Cat. No.01CH37181))

Improved setpoint adjustment for ultrasonic motors - Schulte, T.; Fröhleke, N. (2001 IEEE/ASME International Conference on Advanced Intelligent Mechatronics. Proceedings (Cat. No.01TH8556))

Pitch analysis and control design for the linear motor of a railway carriage - Yang, Bo; Henke, M.; Grotstollen, H. (IEEE Industrial Application Society International Conference (IAS01), Chicago, Illinois, USA)

Enhanced Analysis and Design Issues of a 3 Level DC/DC Converter with Zero Voltage Zero Current Switching - Fröhleke, N.; Schniedermann, M. (9th European Conference on Power Electronis and Applications (EPE01), Graz, Austria)

Development of Power Converter for High Power Piezoelectric Motors - Schulte, T.; Fröhleke, N. (MAGELEC 2001 2nd symposium on electroactive materials and their applications in electrical engineering,Toulouse, France)

Optimization of Inductors in Power Converters Feeding High Power Piezoelectric Motors - Njiende, H.D; Fröhleke, N. (Australian University Power Engineering Conf. (AUPEC'01), Perth, Australia)

Umfangslogik/Inhaltslogik - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Universalsprache - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Use/Mention - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 11: U–V)

Giuseppe Peano, Geometric Calculus According to the Ausdehnungslehre of H. Grassmann. Translated by Lloyd C. Kannenberg. Boston/Basel/Berlin: Birkhäuser 2000 - Peckhaus, Volker (Berichte zur Wissenschaftsgeschichte)

Hilbert’s Paradox - Peckhaus, Volker; Kahle, Reinhard (Reports Institut Mittag-Leffler)

Automatisierte Optimierung von induktiven Bauelementen für Stromrichteranwendungen - Wallmeier, Peter

Leibniz, Gottfried Wilhelm. "Die Grundlagen des logischen Kalküls: Lateinisch–deutsch, herausgegeben, übersetzt und mit einem Kommentar versehen von Franz Schupp", Meiner: Hamburg 2000 (Philosophische Bibliothek; 525) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Wehmeier, Kai F., “Consistent Fragments of Grundgesetze and the Existence of Non-logical Objects”, In: Synthese 121 (1999), 309–328 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Kvasz, Ladislav, “Changes of Language in the Development of Mathematics”, In: Philosophia Mathematica (3) 8, Nr. 1 (2000), 47–83 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Schirn, Matthias (Hg.), "Frege: Importance and Legacy", Walter de Gruyter: Berlin 1996 (Perspectives in Analytical Philosophy; 13) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Heintz, Bettina. "Die Innenwelt der Mathematik. Zur Kultur und Praxis einer beweisenden Disziplin", Springer: Wien 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Atten, M.S.P.R., "Phenomenology of Choice Sequences", Zeno: Utrecht 1999 (Diss. Universität Utrecht 1999) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard. "Wissenschaftslehre §§ 579–718", hg. v. Jan Berg, Friedrich Frommann–Günther Holzboog: Stuttgart-Bad Cannstatt 2000 (Bernard Bolzano-Gesamtausgabe. Reihe I: Schriften. 14.3) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Janssen, Theo M.V., “Frege, Contextuality and Compositionality”, In: Journal of Logic, Language and Information 10, No. 1 (2001), 115–136 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hintze, Henning. "Nominalismus. Primat der ersten Substanz versus Ontologie der Prädikation", Alber Verlag: Freiburg/München 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Carnap, Rudolf. "Untersuchungen zur allgemeinen Axiomatik", hg. v. Thomas Bonk und Jesus Mosterin, Wiss. Buchgesellschaft: Darmstadt 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Pelletier, Francis Jeffry, “Did Frege Believe Frege’s Principle?”, Journal of Logic, Language, and Information 10 (2001), 87–114 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gefwert, Christoffer. "Wittgenstein on Mathematics, Minds and Mental Machines", Ashgate: Aldershot u.a. 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casti, John L./DePauli, Werner. "Gödel: A Life of Logic", Perseus Publishing: Cambridge, Mass. 2000 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Beaney, Michael (Hg.), "The Frege Reader. Selected Philosophical Writings", Blackwell: Oxford 1997 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bueno, Otávio, “What is Structural Empiricism? Scientific Change in an Empiricist Setting”, In: Erkenntnis 50 (1999), 59–85 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Grosholz, Emily/Yakira, Elhanan. "Leibniz’s Science of the Rational", Franz Steiner: Stuttgart 1998 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Spade, Paul Vincent (Hg.), "The Cambridge Companion to Ockham", Cambridge University Press: Cambridge 1999 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Phraseologische Substitution und ihre Funktionen im Text - Ptashnyk, Stefaniya (Wirkendes Wort. Deutsche Sprache und Literatur in Forschung und Lehre. Heft 3/2001)

Фразеологiчні модифiкацiї: термінологічні проблеми [Phraseologische Modifikationen: Terminologische Probleme – ukr.] - Ptashnyk, Stefaniya (Вісник Львівського університету. Випуск 9: Серія іноземні мови)

Gabriel, Gottfried/Kienzler, Wolfgang (eds.), "Frege in Jena. Beiträge zur Spurensicherung. Tagungsbericht, Jena, Deutschland, 6.–7. Dezember 1996", Königshausen & Neumann: Würzburg 1997 - Peckhaus, Volker (Mathematical Reviews [Reprint von Zbl. 897.01002])

van Dalen, Dirk, “The Role of Language in Brouwer’s Work”, in: Ewa Orłowska (Hg.), Logic at Work. Essays Dedicated to the Memory of Helena Rasiowa, Physica-Verlag: Heidelberg 1999, 3–14 - Peckhaus, Volker (Mathematical Reviews)

„Grammatik in Deutsch-Lehrwerken“. Germanisten - Tagung in Karpacz (5.- 7. Sep-tember 2000) - Ptashnyk, Stefaniya; Fraczek, Agnieszka (Convivium. Germanistisches Jahrbuch Polen 2001)

Diagrammatic self-energy approximations and the total particle number - Schindlmayr, Arno; García-González, Pablo; Godby, Rex William (Physical Review B)
There is increasing interest in many-body perturbation theory as a practical tool for the calculation of ground-state properties. As a consequence, unambiguous sum rules such as the conservation of particle number under the influence of the Coulomb interaction have acquired an importance that did not exist for calculations of excited-state properties. In this paper we obtain a rigorous, simple relation whose fulfilment guarantees particle-number conservation in a given diagrammatic self-energy approximation. Hedin’s G0W0 approximation does not satisfy this relation and hence violates the particle-number sum rule. Very precise calculations for the homogeneous electron gas and a model inhomogeneous electron system allow the extent of the nonconservation to be estimated.